Using E-Portfolio to Enhance Students’Motivation Towards Learning English at University College of Applied Sciences, Palestine - Al-Hidabi, Dawood Abdulmalek Yahya; Kabilan, Muhammad K.; Shakfa, Mahmoud D. (2019)
In the era of globalization and technological revolution, the widely spread usage of e-portfolio inside and outside classrooms has encouraged educators and policymakers to look for new methods of assessment that suit the new digital generation.The purpose of this study is to examine the outcome of using e-portfolio on University College of Applied Sciences (UCAS) students' motivation towards English language learning. The total number of students in English Language social work classes under the humanitarian department at UCAS is 60 (30 males and 30 females). Those are officially enrolling in English Language course (DIPL 1303) at first semester of 2014/2015 academic year. A Sequential Exploratory Design was used to collect qualitative and quantitative data for one semester. The results of this study showed that instrumental and integrative motivation levels of UCAS students improved towards learning English after utilizing e-portfolio. But the integrative motivation was found to be a bit higher than instrumental motivation. This has generated several theoretical, pedagogical and policy implications for instructors, universities and researchers. Therefore, it can be concluded that integrating e-portfolio at the tertiary level would improve the potentialities of researchers and policy makers to create a real change in the learning process.